Calcium dependence of uni-quantal release latencies and quantal content at mouse neuromuscular junction - Samigullin, D; Bukharaeva, E A; Vyskocil, F; Nikolsky, E E (Physiological research, 2005)
Uni-quantal endplate currents (EPC) were recorded at mouse diaphragm neuromuscular synapse by extracellular microelectrode during motor nerve stimulation. The probability of release expressed as quantal content m(o), and variability of synaptic latencies expressed as P90 were estimated in the presence of extracellular calcium ([Ca2+]o) varying between 0.2 and 0.6 mM in the bathing solution. At 0.2 mM ([Ca2+]o), m(o) was low (0.10) and many of long-latency EPCs were present during the late phase of the release (P90 = 2.44 ms). No change in m(o) was found when ([Ca2+]o) was 0.3 mM, but P90 decreased by 39 %. For latency shortening, saturating concentration of ([Ca2+]o) was 0.4 mM, when P90 was 1.49 ms and latencies did not further change at 0.5 and 0.6 mM ([Ca2+]o). In the latter concentrations, however, an increase of m(o) was still observed. It can be concluded that the early phase of the secretion did not significantly change when ([Ca2+]o) was raised and that only the late phase of the release depends on extracellular calcium up to 0.4 mM.
Keywords: Animals; extracelulární prostor; Female; reakční čas; ženské pohlaví; Action Potentials; Extracellular Space; Mice; vápník; myši; Calcium; Male; Diaphragm; nervový přenos; Synaptic Transmission; Reaction Time; nervosvalové spojení; Neuromuscular Junction; zvířata; mužské pohlaví; bránice; akční potenciály